VOCABULARY DEPTH KNOWLEDGE AND ACADEMIC READING COMPREHENSION OF BUSINESS EFL UNDERGRADUATES: A CORRELATIONAL DESIGN STUDY - Hasan, Md. Kamrul; Ibna Seraj, Prodhan Mahbub; Chakma, Mekhala (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: An in-depth investigation of vocabulary depth knowledge by lexical researchers plays an important role in language learning and teaching. The present study examined vocabulary depth knowledge of Business EFL learners and its correlation and prediction to academic reading comprehension, employing morphological knowledge and analytical relations with syntagmatic and paradigmatic relations as part of vocabulary depth knowledge. Methodology: The study employed standard multiple regression analysis under a quantitative approach among 120 Business undergraduate EFL students at the tertiary level. Main Findings: Results showed vocabulary depth knowledge, i.e., syntagmatic and paradigmatic relations, had the strongest and significant correlation with reading comprehension compared to other independent variables. Significantly, vocabulary knowledge, combined with paradigmatic and syntagmatic relations, was found to be a significant and unique predictor of academic reading comprehension. About 62.2 percent of the variance in academic reading comprehension was explained jointly by all three independent variables. About 32 percent of the variance was explained by the vocabulary depth knowledge test alone. Also, syntagmatic and paradigmatic relations, representing the depth of vocabulary knowledge test made the most significant unique contribution (uniquely explained about 20.25 percent) to explaining academic reading comprehension in comparison with other dimensions of vocabulary depth knowledge. These findings were elaborated in the perspective of combined paradigmatic and syntagmatic relations as the depth of vocabulary knowledge, derivative word forms as morphological knowledge, part-whole relations as analytic relations and their relationship and contribution to reading comprehension. Applications of this study: The study suggests that the depth of vocabulary knowledge would have a practical use for the students, English teachers at the tertiary level and further implications for lexical researchers. Novelty/Originality of this study: The inclusion of analytic relations with paradigmatic and syntagmatic relations and morphological knowledge, which represented the depth of vocabulary knowledge, has added to the body of lexical knowledge.